PENGARUH WORKING CAPITAL TURNOVER, LONG TERM DEBT TO EQUITY RATIO, DAN RETURN ON EQUITY TERHADAP RETURN SAHAM (Studi pada perusahaan-perusahaan manufaktur sub sektor makanan dan minuman tahun 2009 – 2013) - admin, Wulan Yulianie B11111122 (Jurnal Manajemen Update, 2016)
Investors that put their money by purchasing stock in the capital market will analyze the existing condition of companies in order that their investment can provide reasonable rate of return. Financial statement ratios can give information about the current condition of monetary health of the company. For investors, the financial safety factor of any company could be a consideration to investment choice, as this type of company is expected to give high-return for its investors. This study aims to analyze the effect of working capital turnover, long term debt to equity ratio, and return on equity on stock returns. Population in this study is food and beverages companies which are listed in BEI during 2009-2013, which were obtained from Indonesian Capital Market Directory (ICMD) and IDX (Indonesian Stock Exchanges) stock price information website (www.idx.co.id). By employing purposive sampling technique, the final sample obtained is 11 companies. The analysis technique used was multiple regression analysis. The result of analysis show that return on equity has a positive and significant impact on stock returns, while long term debt to equity ratio and working capital turnover respectively has a negativ and insignificant impact on stock returns. Keywords : stock return, working capital turnover, long term debt-to-equity ratio, return on equity